Evolution and efficacy of use of indicators for improving goat pastoral farms - Mena Y.; Ruíz F.A.; Castel J.M.; Gutiérrez R.; Toussaint G.-C. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Dairy goat grazing systems in the Mediterranean basin are in recession due to the lack of profitability. An improvement of farm management could contribute to optimize the use of resources and to decrease the farm production costs. On the other hand, information based on environmental and social externalities of the farms and the quality of their products, can increase farm incomes. According to that and in order to generate information which can be used for developing strategies to ensure goat pastoral farms continuity, a team of researchers from the Animal Production Area of the University of Seville in 2001 started a colaborative work with the FAO-CIHEAM Subnetwork on Sheep and Goat Production Systems. Researchers of IFAPA were also incorporated in 2005. From 2001 to 2012 relevant information was generated and several improvements of the methodology were done. Initially, retrospective analysis were used. After that, monthly monitoring was employed for collecting information. At the end, environmental and social indicators, which also include information about quality of the products, were incorporated. This paper aims to show the evolution of the methods and tools used, as well as the results obtained and the relationship among researchers, farmers and financial supports.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)